PENGARUH KEPEMIMPINAN DAN MOTIVASI KERJA TERHADAP DISIPLIN KERJA PEGAWAI (SEBUAH KAJIAN EKONOMI SUMBER DAYA MANUSIA STUDI KASUS PADA PT. BANK MUAMALAT INDONESIA CABANG PEMATANGSIANTAR) - Fauzan, Muhammad (Universitas Muhammadiyah Yogyakarta, 2017)
The aim of this study is to determine the effect of leadership and motivation to employees’ discipline in PT. Bank Muamalat Indonesia Pematangsiantar branch. The data collection method of the research is conducted by distributing questionnaires to 25 employees of PT. Bank Muamalat Indonesia Pematangsiantar branch. Leadership (X1) and motivation variable (X2) simultaneously have a positive and significant impact on employees’ discipline in PT. Bank Muamalat Indonesia Pematangsiantar branch. It can be seen from the value of Ftest = 3.287 Ftabel = 3.101. At the level of error α = 5%, the value of the Ftest was significant, with significance = 0.411 error level α = 5%. T-test for leadership variable (X1) is 0.676, for employee’s motivation variable (X2) is 0.875. Based on the hypothesis of criteria if ttest ttabel then H0 is accepted; and H1 is rejected. From determination, identification is known that the correlation coefficient of 0.550 which showed a very strong relationship in which the coefficient of determination (adjusted R2) for 0.379 is between 0 ≤ R2 ≤ 1. And it can be concluded that the variables of leadership and working motivation of employees have a significant effect on employees’ discipline at PT. Bank Muamalat Indonesia Pematangsiantar branch.